The effect of fatigue crack rate on the heat dissipation in metals under mixed-mode loading (Fracture and Structural Integrity, 2019)
The monitoring of a heat dissipation process can give an important information about kinetics of deformation process and current crack propagation rate. The work is devoted to the theoretical and experimental study of the problem. The estimation of the heat sources during the mechanical test was carried out based on infrared temperature measurements combined with an additional system for direct monitoring of a heat flow. To propose the phenomenological description of evolution of plastic work (energy dissipation) at the crack tip under arbitrary loading conditions we used a relations introduced by Dixon in 1965. To illustrate the abilities of the proposed approximation we compare the derived equation with the results of fatigue crack propagation test in flat titanium Grade 2 specimens. The theoretical and experimental results give a good quantitative agreement.
Keywords: Energy dissipation; Crack propagation; Infrared thermography; Mixed-mode loading